Impact of diabetes mellitus on dental implants: A cross sectional controlled clinical study. - Rezhna Muhammed Hamad-Ameen; Othman Abu-Bakr Omer (Erbil Dental Journal)
Background and objective: After osseointegration the long-term success of dental implants is determined by the maintenance of the peri-implant soft tissue and bone level. This study evaluates the impact of Diabetes mellitus on dental implants in diabetic patients and compare it with that of nondiabetic patients. Patients and methods: Thirty diabetic patients and thirty controlled subjects rehabilitated with dental implants were included in this study. The duration of implant treatment is (1-7) years, and dental implant status between both groups was compared using Immunohistochemistry for analyzing Interleukin 6 in peri-implant crevicular fluid, bacteriology, radiology, and clinically by measuring gingival sulcus depth, bleeding on probing, gingival recession, presence of suppuration and mobility. The statistical package for the social sciences program (SPSS, version 28) was used for data analysis. Results: Diabetic patients show a Statistically significant difference to non diabetic subjects in the level of interleukin 6 with (P value 0.004), Culture and sensitivity with (P value 0.003), Peri -implant bone loss in mesial and distal sides of the implant with P values 0.006 and 0.002 respectively, and also, in gingival recession with (P value 0.017). while the difference was not significant in gingival sulcus depth P value0.220, bleeding on probing P value0.550, implant suppuration P value 0.999, and mobility P value 0.999.